1954
DOI: 10.1103/physrev.93.1182
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivity and Solubility of Copper in Germanium

Abstract: The diffusivity and solubility of Cu in Ge have been investigated as a function of temperature in the temperature range 700°-900°C, both by resistivity and radio-activity methods. The average diffusivity is 2.8±0.3X10~5 cm 2 /sec in this temperature interval. The solubility shows a maximum of 4.0X10 16 atoms of copper cm -3 at about 875°C. The precision is not sufficient to determine an activation energy for diffusion. However, calculations based upon a theory of Wert and Zener, indicate an activation energy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

1960
1960
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(36 citation statements)
references
References 24 publications
3
32
1
Order By: Relevance
“…The presence of Cu 3 Ge tips on the NWs confirms they are formed via a solid seeding mechanism as NW growth was conducted far below the Cu/Ge eutectic point of 644 °C. 34 The irregular seed geometry observed here has previously been noted for Cu 3 Ge seeded Ge NWs 12 and is in contrast to the typically observed, hemispherical seeds for Au seeded NWs. 32 Upon closer inspection, it was found that the Cu 3 Ge catalyst seeds had two specific orientations relative to the <110> NWs.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…The presence of Cu 3 Ge tips on the NWs confirms they are formed via a solid seeding mechanism as NW growth was conducted far below the Cu/Ge eutectic point of 644 °C. 34 The irregular seed geometry observed here has previously been noted for Cu 3 Ge seeded Ge NWs 12 and is in contrast to the typically observed, hemispherical seeds for Au seeded NWs. 32 Upon closer inspection, it was found that the Cu 3 Ge catalyst seeds had two specific orientations relative to the <110> NWs.…”
Section: Resultscontrasting
confidence: 51%
“…The presence of Cu 3 Ge tips on the NWs is a clear indicator that a VSS mechanism is responsible for the sub-eutectic growth presented (Cu/Ge eutectic point exists at 644 °C 34 ). We have shown that two specific seed orientations are responsible for the <110> grown NWs which is important given the recent interest in the transfer of crystallographic information from solid catalyst seeds to the resultant NWs.…”
Section: Resultsmentioning
confidence: 99%
“…Such a trap level is a potential non-radiative recombination pathway [11,12]. However, while Cu diffusion and the effects of Cu in large semiconductor crystals are described elaborately in literature [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29], there is virtually no literature on the effects of Cu diffusion on semiconductor devices such as solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oxygen can improve the mechanical strength of Si crystal by inhibiting the glide of dislocations that may unintentionally be introduced during wafer processing. At around 450 • C, oxygen atoms in CZ-Si can form small electrically active agglomerates commonly known as "thermal donors", TDs [2]. Furthermore, oxygen atoms in CZ-Si subjected to heat treatments can aggregate to form oxygen precipitates in bulk Si, acting as "intrinsic gettering" centers for metallic impurities so that defect-free denuded zone can be generated.…”
Section: Introductionmentioning
confidence: 99%